Detecting social changes in times of superdiversity: an ethnographic linguistic landscape analysis of Ostend in Belgium. Issue 5 (8th April 2016) - Maly, Ico
ABSTRACT: Superdiversity, on the one hand, calls for new frames, concepts, and methodologies to deal with a fluid reality characterised by rapid (social) changes. On the other hand, we also have a need to broaden our scope beyond the heavy focus on the urban metropolis as the locus of superdiversity. With this paper I want to contribute to the research addressing these challenges by infusing existing research within Linguistic Landscape Studies with a semiotic and ethnographic perspective and add to our existing knowledge of superdiversity by focusing on a 'small' Belgian city called Ostend instead of a cosmopolitan world city with millions of inhabitants. I argue that ethnographic linguistic landscape analysis (ELLA) enables us to describe, quite accurately, rapid social changes in complex superdiverse neighbourhoods. Moreover, ELLA enables us to move beyond a mere synchronic picture of superdiverse neighbourhoods and sketch a 'stratigraphy' and a historical perspective on them.